Footprints, Movement, and ‘the Road We’re Already On’: From Robinson Crusoe (1719) to Oryx and Crake (2003) - Tynan, Avril (India, 2025)
In Daniel Defoe's Robinson Crusoe (1719), the protagonist's discovery of a single footprint on the beach of the island where he has been marooned for fifteen years is one of literature's most iconic scenes. Remarkable at once for its alterity and its singularity, the footprint refuses to take up position in a series that might help to identify either the origin or the destination of its maker. In Margaret Atwood's post-apocalyptic novel Oryx and Crake (2003), the protagonist's discovery of a trail of (human) footprints liberates the footprint as a trace of erstwhile existence and suggests the movement of what Tim Ingold terms human 'becoming'. Yet the ambiguity of the novel's conclusion draws an ambivalent reading of the path laid out by these footprints, which may not lead us towards moral and epistemological advance but rather to social and environmental catastrophe. Keywords: Daniel Defoe, Margaret Atwood, Tim Ingold, post-apocalyptic fiction, speculative fiction